Wideband patch antenna design using selective particle swarm optimization - Md, Moniruzzaman; Islam, Md Rafiqul; Kamaruzzaman, Sopian; Zaidi, Saleem H (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2012)
This paper presents an optimization technique for wideband patch antennas using selective particle swarm optimization (SPSO). SPSO is an improved variant of particle swarm optimization (PSO). Here, a special part of solution space is selected for PSO process. An application of this algorithm is developed for wideband patch antenna optimization. A stripes based antenna is designed by utilizing this algorithm. The performance of the antenna is observed by industry standard electromagnetic simulation software. The antenna shows 41.8 % bandwidth at -10 dB return loss, which is suitable for wideband applications.